Factors Affecting Consumption Households in Indonesia: Faktor-Faktor Yang Mempengaruhi Konsumsi Rumah Tangga Di Indonesia - Komalawati; Anggi Sahru Romdon; Zumi Saidah (Program Studi Agribisnis Universitas Sumatera Selatan, 2021)
Consumption is one of the important factors in aggregate expenditure and has a major contribution to the economic growth of a country. Many factors affect the level of household consumption. For this reason, this paper is intended to examine the factors that influence the level of household consumption in Indonesia by referring to several existing consumption theories. The data used is time series data obtained from the Central Statistics Agency, and processed using the Ordinary Least Square (OLS) method. The results of the analysis strengthen the initial Keynesian theory which shows that a significant factor influencing household consumption is disposable income.